Thermochemical upgrading of coconut husk and rubber seed to coal co-firing feedstock via torrefaction - Lee, Y.T.; Ng, H.K.; Jourabchi*, Seyed Amirmostafa (IOP Publishing, 2019)
This research seeks to investigate thermochemical upgrading of Malaysian coconut husk and rubber seed to coal co-firing feedstock via torrefaction. Torrefaction experiments within a range of temperatures (200-300°C) and holding times (30 and 60 min) were carried out using a tubular furnace. Mass yield, higher heating value (HHV), energy densification ratio (EDR) and energy yield as well as proximate analysis were determined for the torrefied biomass sample. Both torrefaction temperature and holding time decreased the mass yield and the energy yield of the torrefied biomass. The HHV and EDR of coconut husk and rubber seed increased upon torrefaction. The VM decreased while the FC increased after torrefaction. Rubber seed torrefied at 300°C and 60 min had a HHV of 29.22 MJ/kg which was comparable to that of bituminuous coal. Linear correlations (R2=0.7764-0.965) were developed between mass yield and EDR, as well as mass yield and energy yield. Up to 70 wt% and 60 wt% of coal with a fuel ratio of 1 could be replaced by coconut husk and rubber seed torrefied at 300 °C and 60 min, respectively. Overall, the study indicated the feasibility of torrefied rubber seed (300°C and 60 min) as a coal co-firing feedstock in comparison to torrefied coconut husk due to its higher HHV cum lower ash content as well as its high co-firing proportion with coals having fuel ratio of at least 1.